2004
DOI: 10.1176/appi.ajp.161.9.1672
|View full text |Cite|
|
Sign up to set email alerts
|

Health Correlates of Recreational Gambling in Older Adults

Abstract: Recreational gambling patterns of older adults differ from those of younger adults. In contrast to findings in younger adults, recreational gambling in older adults is not associated with negative measures of health and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 15 publications
8
115
2
3
Order By: Relevance
“…Individuals who reported never having gambled more than 5 times in a given year were categorized as "non-gamblers." As in prior studies 1,25,26 , NODS scores were used to categorize gamblers into recreational (NODS=0-2), and problem/pathological (NODS=3+) gamblers.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who reported never having gambled more than 5 times in a given year were categorized as "non-gamblers." As in prior studies 1,25,26 , NODS scores were used to categorize gamblers into recreational (NODS=0-2), and problem/pathological (NODS=3+) gamblers.…”
Section: Methodsmentioning
confidence: 99%
“…As such, bus tours are a disproportionately popular way for older adults to access gambling venues. For example, an intercept study of casino gamblers in the American Midwest found that 64.7% of those over the age of 65 years had come to the casino through an organized bus trip compared to younger cohorts, which ranged from 5.1% (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) to 17.7% (55-64) [4]. To date, one Australian study has found an association between the perceived importance of shuttle service and problem gambling.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, constatou que os idosos que jogaram no último ano, apresentavam maior chance de relatar uso de álcool no último ano do que os que não jogaram. O jogo não estava associado a medidas negativas de saúde e bem-estar, e a auto-avaliação de saúde geral tida como boa ou ótima nos jogadores recreacionais foi do grupo mais velho (Desai et al, 2004). Outra pesquisa feita com idosos de 71 a 97 anos Jogo problemático ou patológico e a correlação com consumo de substâncias nos idosos Petry (2002) pesquisou jogadores em tratamento nos Estados Unidos, categorizando a amostra em: jovens (18 a 35 anos), adultos (36 a 55 anos) e mais velhos (acima de 55 anos).…”
Section: Resultsunclassified